Exegetical Narratives in Sunan Al-Darami (T.: 255 AH) Surat Al-Imran and Al-Ma’idah- A Model (a Comparative Interpretive Study) - Sabr, Muhammad; Hassoun , Uday (Islamic Sciences Journal, 2023)
ABSTRACT This research aims to shed light on the most important hadiths mentioned by Imam Al-Darimi (may Allah have mercy on him) in the chapter of interpretation, and to clarify the scientific status of Imam Al-Darimi, and his status among scholars, as well as the combination of the Holy Qur’an and its interpretation with the Prophet’s Sunnah, and its explanations through this study, and looking forward to understanding the verses of the Noble Qur’an, by understanding the hadiths contained in its interpretation.